An Examination of Parental Permissiveness of Alcohol Use and Monitoring, and Their Association with Emerging Adult Drinking Outcomes Across College. (8th March 2019) - Mallett, Kimberly A.; Turrisi, Rob; Reavy, Racheal; Russell, Michael; Cleveland, Michael J.; Hultgren, Brittney; Larimer, Mary E.; Geisner, Irene M.; Hospital, Michelle
Abstract : Background: Studies have shown that parents have a significant influence on emerging adult college students' drinking during the first year of college. Limited research has been conducted to address the question of whether parenting later in college continues to matter in a similar manner. The current study utilized a prospective design to identify associations between parental permissiveness toward alcohol use and monitoring behaviors and student drinking outcomes during the first and fourth years of college. Methods: Participants ( N = 1, 429) at 3 large public universities completed surveys during the fall semesters of their first (T1) and fourth years (T2) (84.3% retention). The study employed a saturated autoregressive cross‐lag model to examine associations between parental permissiveness of college student alcohol use, parental monitoring, student drinking, and consequences at T1 and T2, controlling for peer norms, sex, and campus. Results: Examination of the association between parenting and student drinking outcomes revealed: (i) parental permissiveness was positively associated with drinking at T1 and again at T2; (ii) parental permissiveness had indirect effects on consequences via the effects on drinking at both times. Specifically, a 1‐unit increase in parental permissiveness at T1 resulted in students experiencing 4 to 5 more consequences as a result of their drinking; (iii) parental permissiveness was not directly associated with monitoring at T1 or T2; and (iv) parental monitoring was significantly associated with drinking at T1 but not T2. Conclusions: The findings provide evidence for the continued importance of parenting in the fourth year of college and parents expressing low permissiveness toward student drinking may be beneficial to reducing risky drinking even as students turn 21. Abstract : The study examined associations between parental permissiveness toward alcohol use and monitoring behaviors and student drinking outcomes during the first and fourth years of college. Consistent with previous work, both parental behaviors were associated with student drinking early in college. However, findings demonstrated the continued importance of parental permissiveness in the fourth year of college. Specifically, students with less permissive parents reported less drinking and fewer consequences even after turning 21.